Global economic costs of herpetofauna invasions - Soto, Ismael; Cuthbert, Ross N; Kouba, Antonín; Capinha, César; Turbelin, Anna; Hudgins, Emma J; Diagne, Christophe; Courchamp, Franck; Haubrock, Phillip J (Scientific reports, 2022)
Biological invasions by amphibian and reptile species (i.e. herpetofauna) are numerous and widespread, having caused severe impacts on ecosystems, the economy and human health. However, there remains no synthesised assessment of the economic costs of these invasions. Therefore, using the most comprehensive database on the economic costs of invasive alien species worldwide (InvaCost), we analyse the costs caused by invasive alien herpetofauna according to taxonomic, geographic, sectoral and temporal dimensions, as well as the types of these costs. The cost of invasive herpetofauna totaled at 17.0 billion US$ between 1986 and 2020, divided split into 6.3 billion US$ for amphibians, 10.4 billion US$ for reptiles and 334 million US$ for mixed classes. However, these costs were associated predominantly with only two species (brown tree snake Boiga irregularis and American bullfrog Lithobates catesbeianus), with 10.3 and 6.0 billion US$ in costs, respectively. Costs for the remaining 19 reported species were relatively minor (< 0.6 billion US$), and they were entirely unavailable for over 94% of known invasive herpetofauna worldwide. Also, costs were positively correlated with research effort, suggesting research biases towards well-known taxa. So far, costs have been dominated by predictions and extrapolations (79%), and thus empirical observations for impact were relatively scarce. The activity sector most affected by amphibians was authorities-stakeholders through management (> 99%), while for reptiles, impacts were reported mostly through damages to mixed sectors (65%). Geographically, Oceania and Pacific Islands recorded 63% of total costs, followed by Europe (35%) and North America (2%). Cost reports have generally increased over time but peaked between 2011 and 2015 for amphibians and 2006 to 2010 for reptiles. A greater effort in studying the costs of invasive herpetofauna is necessary for a more complete understanding of invasion impacts of these species. We emphasise the need for greater control and prevention policies concerning the spread of current and future invasive herpetofauna.
Keywords: obojživelníci; Amphibians; North America; ekosystém; plazi; Reptiles; zavlečené druhy; Animals; lidé; Ecosystem; zvířata; Humans; Introduced Species; Severní Amerika